Minimization of load variance in power grids-investigation on optimal vehicle-to-grid scheduling - Tan K.M.; Ramachandaramurthy V.K.; Yong J.Y.; Padmanaban S.; Mihet-Popa L.; Blaabjerg F. (MDPI AG, 2023)
Battery management systems; Electric automobiles; Electric vehicles; Energy management; Fleet operations; Genetic algorithms; Global warming; MATLAB; Optimization; Scheduling; Software testing; Vehicle performance; Vehicle-to-grid; Carbon emissions; Grid optimization algorithms; Optimal scheduling; Optimization algorithms; Research proposals; Smart Grid technologies; Transportation sector; Variance minimization; Electric power transmission networks